Cerebral time domain-NIRS: reproducibility analysis, optical properties, hemoglobin species and tissue oxygen saturation in a cohort of adult subjects - Giacalone, Giacomo; Zanoletti, Marta; Contini, Davide; Re, Rebecca; Spinelli, Lorenzo; Roveri, Luisa; Torricelli, Alessandro (Biomedical optics express, 2017)
The reproducibility of cerebral time-domain near-infrared spectroscopy (TD-NIRS) has not been investigated so far. Besides, reference intervals of cerebral optical properties, of absolute concentrations of deoxygenated-hemoglobin (HbR), oxygenated-hemoglobin (HbO), total hemoglobin (HbT) and tissue oxygen saturation (StO ) and their variability have not been reported. We have addressed these issues on a sample of 88 adult healthy subjects. TD-NIRS measurements at 690, 785, 830 nm were fitted with the diffusion model for semi-infinite homogenous media. Reproducibility, performed on 3 measurements at 5 minutes intervals, ranges from 1.8 to 6.9% for each of the hemoglobin species. The mean ± SD global values of HbR, HbO, HbT, StO are respectively 24 ± 7 μM, 33.3 ± 9.5 μM, 57.4 ± 15.8 μM, 58 ± 4.2%. StO displays the narrowest range of variability across brain regions.